PREVALENCE OF ATOPIC DERMATITIS IN CHILDREN IN RUSSIAN FEDERATION - Yu.A. Gallyamova; M.P. Chernysheva; Yu.B. Tikhonova ("Paediatrician" Publishers LLC, 2009)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(2):122-123)